1996
DOI: 10.3354/meps138041
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of total mercury concentrations and burdens in the liver of eelpout Zoarces viviparus from the Forth Estuary, Scotland:implications for mercury biomonitoring

Abstract: The utility of fishes a s biomonitors for mercury in aquatic environments is widely recognised, with skeletal muscle a s the tissue normally chosen for most monitoring programmes. The liver may also be a suitable candidate tissue for monitoring, as it concentrates many pollutants to higher levels than muscle, and is closely involved with processes of metal dynamics, storage, and detoxification. Little consideration has been given previously to the validation of the use of liver for mercury biomonitoring, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…This distribution pattern was previously shown for several metals and volatile chlorinated compounds in the Scheldt [11,23,24]. Seasonal variation in eelpout (Zoarces viviparus) liver mercury burden results largely from the dilution of similar burdens by a seasonally growing and shrinking liver, illustrating the possible impact of tissue dilution on concentrations of toxicants in fish tissues [28]. These authors observed a concentration gradient for a number of metals in the soft body tissues of the periwinkle (Littorina littorea) paralleling their Western Scheldt pollution gradient.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This distribution pattern was previously shown for several metals and volatile chlorinated compounds in the Scheldt [11,23,24]. Seasonal variation in eelpout (Zoarces viviparus) liver mercury burden results largely from the dilution of similar burdens by a seasonally growing and shrinking liver, illustrating the possible impact of tissue dilution on concentrations of toxicants in fish tissues [28]. These authors observed a concentration gradient for a number of metals in the soft body tissues of the periwinkle (Littorina littorea) paralleling their Western Scheldt pollution gradient.…”
Section: Discussionsupporting
confidence: 72%
“…Solé et al [27] found lower concentrations of several organic pollutants in muscle tissue of deep-sea fish with larger sizes and suggested that tissue dilution might be responsible for this phenomenon. Seasonal variation in eelpout (Zoarces viviparus) liver mercury burden results largely from the dilution of similar burdens by a seasonally growing and shrinking liver, illustrating the possible impact of tissue dilution on concentrations of toxicants in fish tissues [28]. Tissue dilution as a result of changes in nutritional status can also greatly influence tissue concentrations, as was illustrated for cadmium exposure of dogwhelks (Nucella lapillus) [29].…”
Section: Discussionmentioning
confidence: 98%
“…Seasonal variation of Hg content in marine fishes is poorly documented (Greenfield et al, 2013;Kucuksezgin et al, 2001;Mathieson et al, 1996). As Hg has a higher affinity for proteins, muscle displays a higher Hg concentration than gonads (Webb et al, 2006).…”
Section: Temporal Variation Of Hg Concentrationmentioning
confidence: 98%
“…For instance, great sculpin ( Myoxocephalus polyacanthocephalus ) caught off Adak, Alaska, were found to have ratios of 1:1 (muscle–liver) and 3:1 (muscle– kidney) (Burger et al 2007b). A muscle–liver ratio of >1 for [Hg] has been reported in estuarine fish species and elasmobranchs (Mathieson et al 1996; Coelho et al 2010). In adult marine mammals including whales, pinnipeds, and polar bears (Hyvärinen et al 1998; Wagemann et al 1998; Dietz et al 2000; Frodello et al 2000; Moses et al 2009), liver and/or kidney generally have the highest [THg].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, muscle represents a higher percentage of the body weight (larger compartment) than liver or kidneys and is more likely to be preferentially consumed by humans. Even when the [THg] is lower in muscle than in liver, muscle may have a greater proportion of the body burden of Hg (Giblin and Massaro 1973; Mathieson et al 1996; Brookens et al 2008). Thus, if there is concern about the risk of Hg exposure through piscivory, it is critical to include muscle samples in any assessment, and this is particularly important in species where differential tissue-specific distribution of Hg has not been examined.…”
Section: Discussionmentioning
confidence: 99%